Identification of the Type and Density of Macro Solid Waste on the Coast of Kastela Beach, Ternate Island District, Ternate City - Pelu, Ismianti; Putuhena, Jusmy D.; Soselisa, Fanny (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The existence of waste in coastal areas will have an impact on the function of the area, namely as a spawning ground for fish and the productivity of mangrove ecosystems as a barrier to coastal abrasion, breeding grounds and growth of marine biota, as well as a supplier of seafood ingredients for coastal communities. Therefore, this study aims to identify the type and density of solid waste on the Kastela Coast, Ternate Island District, Ternate City. The research method uses qualitative descriptive analysis with calculations of absolute density (number of pieces of waste and weight) and relative density (number of pieces of junk and importance of waste). The results showed that the types of garbage found on the coast of Kastela Beach contained seven types of waste materials, including plastic, plastic foam, cloth, glass and ceramics, metal, paper and cardboard, rubber, and other materials. Plastic is the type of waste material with the highest density value of the six different types of waste materials; based on the number of pieces, the absolute density is 20.6, and the relative density is 73%, while based on weight, the final thickness is 15.16 and the relative density is 39%.